Uganda and REDD+: Is it worth getting involved from a socio-economic perspective? - Lutalo, Proscovia (Energy Research Centre, 2016)
Anthropogenic (human caused) climate change is a major global issue because of the effects of climate change, which include increased frequency of drought, floods, erratic and/or insufficient rainfall, waterborne diseases; as well as related consequences such as water shortages, forest fires and loss of biodiversity. It is therefore imperative that there be a global effort to mitigate climate change in order to limit these potentially disastrous effects. Deforestation and forest degradation, principally in the tropics, cause approximately 12 percent of anthropogenic greenhouse gas (GHG) emissions. Therefore, one method to mitigate climate change is to address reducing GHG emissions from deforestation and forest degradation. "Reducing Emissions from Deforestation and Forest Degradation, conservation, sustainable management of forests, and enhancement of forest carbon stocks in developing countries," also known as REDD+, is, at its core, a financial incentives based strategy that aims to compensate national governments, sub-national actors, private project developers and/or local communities, in return for demonstrable reductions in carbon emissions from deforestation and forest degradation and enhancements of terrestrial carbon stocks. REDD+ also focuses on building capacity for developing countries to reduce emissions from deforestation and forest degradation and invest in low-carbon paths to sustainable development. Uganda is one of the developing countries that has shown enthusiasm for REDD+ and has actively engaged in REDD+ readiness activities. However, REDD+ readiness activities are costly due to various institutional capacity requirements that may pose a significant challenge to Uganda. The question posed by the study is whether Uganda's involvement in REDD+ is likely to result in net economic benefits for the country. The study aims to determine whether, in the absence of direct evidence of the success of the REDD+ mechanism in any country, Uganda's economic benefits from REDD+ are still expected to exceed the costs of implementation. Social benefits are an additional incentive however, even a combination of both economic and social benefits may not be reason enough for a country to become a REDD+ country, especially if alternative land uses are more lucrative or costs are too high. The methodology used is largely qualitative and theoretical, except for the economic analysis which is quantitative. The outcome of the study is that while there is insufficient evidence to suggest that Uganda will not benefit overall from being involved with REDD+, the feasibility study of the potential REDD+ project in the Murchison-Semkili landscape showed that, at least in that project area, the economic benefits were unlikely to cover both the implementation and opportunity costs in the long term. This does raise a legitimate concern that REDD+ might not result in net economic benefits for Uganda. Even though the economic benefits of Uganda's involvement in REDD+ are uncertain, the mechanism is still expected to result in social benefits, such as improved livelihoods in terms of service delivery; increased efficiency and accountability of government and governmental institutions; and increased public consultation and participation. There are, however, risks to Uganda's successful implementation of REDD+ such as unspecified donor funding, which may not be forthcoming, and the lack of clarity surrounding global compliance carbon markets. Uganda still has much to do in order to build the required institutional capacity for REDD+ to be successful, especially with regard to increasing the effectiveness of the institutions that manage the country's forests. Uganda also needs to reduce some of the drivers of deforestation in the country through programmes that target poverty alleviation and improve agricultural practices. In terms of REDD+ specifically, Uganda needs to complete the development of a National REDD+ Strategy, secure adequate funding for the mechanism, and accelerate the development of REDD+ pilot activities, which are currently in the planning phase. Further research is needed on determining the total value of Uganda's forests, taking into account economic, environmental and social considerations. Research is also needed on the impact successful REDD+ pilot activities have had in other comparable countries.